(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2025)
The study aimed to assess how third-party funds and customer number affect LPD Desa Adat Ketewel’s profitability. It occurred at the Ketewel Traditional Village LPD and focused on financial reports concerning profits, external funding, and customer number from 2019 to 2023. This study focuses on financial reports from 2019 to 2023, explicitly addressing profitability, third-party funds, and customer numbers. This study employs a census approach to examine the entire population. Data gathering utilized interviewing and documentation methods. Multiple linear regression is utilized as the analysis method. The analysis findings show that third-party funds positively but not significantly influence the profitability of LPD Desa Adat Ketewel, while the customer number negatively but insignificantly affects its profitability.